PENGARUH VAKUM PADA PROSES PEMBUATAN SABUN KALSIUM BERBAHAN BAKU PFAD - Jorgensen
Indonesia is the world's largest producer and exporter of palm oil that produces around 58% of the world's total palm oil production. The process of turning mesocarp into palm oil produces a by-product called Palm Fatty Acid Distillate (PFAD). PFAD contains lots of free fatty acids that are needed by cattle. But free fatty acids need to be converted into calcium soap thus they can be digested properly because they are protected fat. Calcium soap is the result of a saponification reaction between PFAD and calcium oxide (CaO) solids which has been proven to increase milk production and increase cow fertility. This experiment is expected to help solving the problem of low dairy milk production in Indonesia. The purpose of this experiment is to determine the effect of vacuum condition on the process of making calcium soap. The quality of the calcium soap is determined by the acid value and moisture content. The modified fusion method is used to make the calcium soap. The variations in this experiment are vacuum pressure in the system (-10, -20, dan -30 cmHg) dan and the temperature of the mixture when the vacuum system is applied (78, 80, 82, dan 84oC). Based on the mass and heat balance, a temperature profile with respect to time can be calculated and the results are then compared with experimental data. The results of the experiments shows that the acid value of the calcium soap is higher when the system pressure is lower. This can be caused by a vortex due to the mixing process. However, the difference between the acid value of each variation is not significant due it is between 1.25-3.00 mg KOH/g calsium soap. When a higher vacuum pressure is applied, the peak temperature is lower. The lowest moisture content is resulted at the variation of -10 cmHg vacuum pressure pump and the mixture temperature is 80oC. Based on calculation, the difference between calculated temperature and experimental data has a range value of 16.20-19.26% due to the evaporation in the vacuum conditions and the system is not completely insulated.